2005
DOI: 10.1038/sj.pcan.4500845
|View full text |Cite
|
Sign up to set email alerts
|

Novel antiproliferative flavonoids induce cell cycle arrest in human prostate cancer cell lines

Abstract: Epidemiologic studies have demonstrated an inverse association between flavonoid intake and prostate cancer (PCa) risk. The East Asian diet is very high in flavonoids and, correspondingly, men in China and Japan have the lowest incidence of PCa worldwide. There are thousands of different naturally occurring and synthetic flavonoids. However, only a few have been studied in PCa. Our aim was to identify novel flavonoids with antiproliferative effect in PCa cell lines, as well as determine their effects on cell c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
100
1
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 150 publications
(112 citation statements)
references
References 50 publications
9
100
1
2
Order By: Relevance
“…However, matrix degradation by MMPs can alter the basic processes of cell proliferation and apoptosis. The chemopreventive effect of the flavonoids, flavonols (quercetin and kaempferol) and isofl avones (genistein, genistin and daidzein) has been observed through the suppression of cell proliferation [35] , inhibition of angiogenesis [36] , inhibition of invasion [37] and stimulation of apoptosis in breast carcinoma cells [38] . The inhibition of invasion of cancer cells is of great significance in cancer treatment.…”
Section: Discussionmentioning
confidence: 99%
“…However, matrix degradation by MMPs can alter the basic processes of cell proliferation and apoptosis. The chemopreventive effect of the flavonoids, flavonols (quercetin and kaempferol) and isofl avones (genistein, genistin and daidzein) has been observed through the suppression of cell proliferation [35] , inhibition of angiogenesis [36] , inhibition of invasion [37] and stimulation of apoptosis in breast carcinoma cells [38] . The inhibition of invasion of cancer cells is of great significance in cancer treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies demonstrated that fisetin and hesperetin inhibited the proliferation of cancer cells by inducing G2/M or G0/G1 arrest. For instance, fisetin induced G2/M arrest in human epidermoid carcinoma A431 cells [25], HT-29 colon cancer cells [8], and PC3 prostate cancer cells [26]. Human cervical SiHa cells treated with hesperetin displayed G2/M arrest in a dose-dependent manner as well [23].…”
Section: Discussionmentioning
confidence: 99%
“…Dietary flavonoid fisetin, a phytochemical, has been shown in preclinical studies to inhibit cancer growth through alteration of cell cycle (Gupta et al, 2014;Haddad et al, 2005;Lall et al, 2016). Fisetin also showed its beneficial effects against several diseases.…”
Section: Discussionmentioning
confidence: 99%